Virtual idols: A new cultural industry and fan structure. - Wu, Yinhao (Transformative Works & Cultures, 2024)
As a result of the segregation caused by the pandemic, virtual idols have developed as a new entertainment model in China. This emergence has constructed a new subculture of fan groups.